Ways to Improve Information and Consulting Services in the Field of Tourism - Yuldashev Kamol Sharifovich (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2021)
This article analyzes the scientific basis for the development of information and consulting services, explores the role of consulting services in tourism, as well as offers to open a unitary enterprise, the introduction of Internet consulting services and improve training to implement it in the tourism business of Uzbekistan. In the hotel business, as in any other, the main thing is profitability. The purpose of consulting is to provide comprehensive information to the customer (hotelier) for making a decision, to suggest options and describe the risks that are lacking in the hotel business in Uzbekistan. A consultant is primarily a partner, an independent expert (Arsenev Aleksey.2015). Consulting solves the issues of management, economic, financial, investment activities of organizations, strategic planning, optimization of the general functioning of the company, business management, and research and forecasting of sales markets, price movements, etc. Our problem in tourism is that hotel business owners have no idea how to properly set up a hotel management system, which in most cases will lead to hotel bankruptcy.